Student Motivation and Identity Construction in an Intensive U.S. French Immersion Program - Maltais, Alexis (Université d'Ottawa / University of Ottawa, 2012)
This study explores how U.S. college students experience integrative and instrumental motivation and how their sociolinguistic identity is understood, represented and constructed through their multiple experiences learning French as a Foreign Language (FFL) in an intensive Summer French Language Immersion Programs (SFLIPs). The results of the study demonstrate that participants who exhibited the most characteristics in connection to integrative motivation were the ones who took full advantage of the opportunities of being immersed in an environment in which exposure and production of the target language were maximized. The study demonstrates how participants’ lived experiences affect the way they construct their identity, how integrative motivation plays a key role in this construction and addresses a gap in literature by specifically adressing the themes of motivation and identity in the context of intensive French immersion in the U.S.
Keywords: Intensive Immersion; French as a foreign language; Motivation; Identity